Perbandingan Hasil Penggunaan Media Audio Visual dengan Media Gambar Seri dalam Pembelajaran Menulis Teks Prosedur - Muliati Muliati; Akmal Hamsa; Usman Usman (Indonesian Journal of Social and Educational Studies, 2021)
Abstract. This study aims to describe: (1) the results of the use of audio visual media in the learning of writing procedure text, (2) the results of the use of serial image media in the learning of writing procedure text, and (3) the comparison of the results of use between audio visual media and serial image media in the learning of writing text proedur students of Grade VII SMPN 1 Polombangkeng Utara. This type of research is quantitative research using a descriptive comparative approach. The data collection technique in this study is to create learning groups through Whatsapp application, assignments, and assessments. Data analysis techniques are performed by creating frequency and percentage distribution tables, creating tables of accumulated student grades, and creating categorization tables of media usage results. The results of this study showed that: (1) the results of the use of audio visual media in the learning of writing text procedures of Grade VII smpn 1 North Polombangkeng students are categorized well with an average score of 69 students. (2) the results of the use of serial image media in learning to write the text of the procedure of Grade VII SMPN 1 North Polombangkeng students are categorized as good with an average score of 72 students. (3) the results of the use between audio visual media and serial image media are at the same value interval of 60-84 categorized well with the average value of students on the use of audio visual media 69 while in the use of image media series 72. Keywords: text, procedure, learning media.